Assessment of Lithium-Ion Battery Degradation and its impact on ECM using Simulated Impedance Spectroscopy - Jayasinghe, A.E.; Fernando, N.; Kumarawadu, S.; Wang, L.; Karunadasa, J.P. (IEEE, 2024)
This paper investigates Equivalent Circuit Model (ECM) based Impedance Spectroscopy to assess the state of Lithium-Ion Battery (LIB) Degradation. ECM parameter identi- fication under different ageing mechanisms has been considered. The proposed technique is investigated using reference Elec- trochemical Impedance Spectroscopy (EIS) data obtained via a simulated LIB electrochemical model in the Python PyBAMM package. A Genetic Algorithm (GA) based optimization strategy is used to identify the ECM parameters for different ageing mechanisms with calendar ageing. The results show that the ECM is capable of capturing the LIB dynamics over a wide frequency range in addition to identifying the ECM parameter variations for specific degradation mechanisms.
Keywords: Lithium-ion battery; Battery Modelling; Equivalent Circuit Model; Electrochemical Impedance Spectroscopy